Corrosion Under Insulation (CUI): The Absorption Characteristics of Rockwool - Sethulingam, Shivalingam; Ismail, Azzura (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Corrosion under insulation (CUI) is a degradation of metal which has occurrence under the part of the equipment which is insulated. Corrosion under insulation is a major issue that many industries face on a daily basis. In the project, the absorption characteristics of the rockwool sample is studied. For moisture absorption, the sample weight is measured after every 90 drops of water. For drying, five samples were put in a closed beaker, non-closed beaker, heated hotplate at 70  ,soaked in tap water and soaked in tap water and waterbath at room temperature. The closed and non-closed beaker samples is monitored every two days whereas every two hours for the heated hotplate sample. The samples are observed under the Scanning Electron Microscope(SEM) . For moisture absorption, there is saturation at 990 drops of water. For drying, the rockwool sample in the non-closed beaker returned to the initial weight faster and the heated rockwool sample took twelve hours to return to the initial weight. Based on SEM analysis, the surface of the samples showed almost similar morphology. There are some suggestions for future work such as using different insulation materials and the use of constant temperature.